2021
DOI: 10.1001/jamainternmed.2021.2219
|View full text |Cite
|
Sign up to set email alerts
|

Association of Facial Paralysis With mRNA COVID-19 Vaccines

Abstract: The information does not represent the opinions of the Uppsala Monitoring Centre or the World Health Organization. Additional Information:We thank VigiBase for giving us access to the data. The data supplied to VigiBase come from a variety of sources, and the likelihood of a causal relationship is not the same in all reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 6 publications
2
30
1
Order By: Relevance
“…Therefore, by broadening the spectrum of safety reports of interest to those with COVID-19 vaccines (of all technologies) suspected of being associated with FP/BP onset, the present study controverts the one previously performed in VigiBase by Renoud et al, which found that the reporting rate of FP/BP after mRNA COVID-19 vaccines was not higher than that observed with other viral vaccines [12]. In that study, authors used stratification to control confounding factors (including sex and age) and, assuming the absence of risk variation across strata, provided a single combined (not significant) disproportionality measure [12]. Nevertheless, ignoring the diversity within a dataset may result in signals being masked.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore, by broadening the spectrum of safety reports of interest to those with COVID-19 vaccines (of all technologies) suspected of being associated with FP/BP onset, the present study controverts the one previously performed in VigiBase by Renoud et al, which found that the reporting rate of FP/BP after mRNA COVID-19 vaccines was not higher than that observed with other viral vaccines [12]. In that study, authors used stratification to control confounding factors (including sex and age) and, assuming the absence of risk variation across strata, provided a single combined (not significant) disproportionality measure [12]. Nevertheless, ignoring the diversity within a dataset may result in signals being masked.…”
Section: Discussioncontrasting
confidence: 95%
“…Since marketing authorization, cases of NA, FP/BP and GBS were reported with COVID-19 vaccines [4][5][6][7][8][9][10][11]. A recent pharmacovigilance study in VigiBase, the World Health Organization's (WHO) global database of suspected adverse drug reactions (ADRs) found that the reporting frequency of FP/BP with mRNA COVID-19 vaccines was similar to that with other viral vaccines [12].…”
Section: Introductionmentioning
confidence: 99%
“…4 9 A recent disproportionality analysis using the WHO pharmacovigilance database showed no difference between the reporting rate of facial nerve paralysis with COVID-19 mRNA vaccines when compared with other viral vaccines. 10 Unilateral facial nerve palsies occurring after each COVID-19 vaccine dose were not reported in any of the three vaccine trials, nor has this been reported in the literature.…”
Section: Introductionmentioning
confidence: 92%
“…They found no higher safety signal for facial palsy after mRNA Covid-19 vaccines when compared with all other viral vaccines or restricted to influenza vaccines. [58] Eric Wan et al found an overall increased risk of Bell's palsy after vaccinated with CoronaVac, an inactivated virus COVID-19 vaccine, but no increased risk after BNT162b2 vaccination. [59] In our study, we found no elevated risk of Bell's palsy with BNT162b2, but a small increased risk with ChAdOx1.…”
Section: Findings In Contextmentioning
confidence: 99%